REVISION OF MALAYSIAN ORTHOSIPHON (LAB.) - ELLEN VAN DER SLEESEN (BRIN Publishing (Penerbit BRIN), 1959)
In Malaysia the genus Orthosiphon has gained some general interest,because one of its species, well-known under its vernacular name kumis kutjing- or remukdjung, has been recognized as a noteworthy medicinal plant, besides being of some horticultural value.In the recent treatment by ADHLBERT in the emergency edition of Backer's 'Beknopte flora van Java'(1954) three species have been recognized, viz O. petiolaris MIQ., O. aristatiis (BL.) MIQ., and O. stamineus BTH. In my opinion the differences between the latter two are so small that they cannot be recognized as good species; in the herbarium they appear indistinguishable.My study has been based on the specimens in the Leyden and Utrecht herbaria.